REAL OPTION ANALYSIS IN MERGERS & ACQUISITIONS IN INDIAN CONTINENT - Dr. Pramod S. Jadhav; Dr. Suhas B. Pakhare; Dr. Santosh Dhawale; Dr. Rupali Pachpute (Elementary Education Online, 2023)
Aim and Method: The preliminary objective of the study is to verify the strategies used by acquirers in target companies in Indian continent just before recession hit. This will enable us to understand strategies used in recession hit countries and formulate the investments options to expand the scope and scale in country’s top businesses. Moreover, this study helps to highlights the various types of real options encountered in merger and acquisitions. Result and conclusion: It is the analytical cum descriptive study in which various trading options will be thoroughly evaluated on its cumulative impact rate on Indian economy. Researcher found that there are mainly six types of real options are available based on the factors like time, growth, abandonment, expansion scale, input and output switches and contract scales. Furthermore, it has found that timing options are important in all resource extraction in industrial real estate development and paper products. Therefore, researcher conclude that the managing options will be truly depends on factors like when to invest, where to invest and at what stage we should invest.